Circulating miR-320a Acts as a Tumor Suppressor and Prognostic Factor in Non-small Cell Lung Cancer - Khandelwal, Akanksha; Sharma, Uttam; Barwal, Tushar Singh; Seam, Rajeev Kumar; Gupta, Manish; Rana, Manjit Kaur; Vasquez, Karen M.; Jain, Aklank (Frontiers in Oncology, 2021)
Dysregulated expression profiles of microRNAs (miRNAs) have been observed in several types of cancer, including non-small cell lung cancer (NSCLC); however, the diagnostic and prognostic potential of circulating miRNAs in NSCLC remains largely undefined. Here we found that circulating miR-320a was significantly down-regulated ( 5.87-fold; p < 0.0001) in NSCLC patients (n = 80) compared to matched control plasma samples from healthy subjects (n = 80). Kaplan-Meier survival analysis revealed that NSCLC patients with lower levels of circulating miR-320a had overall poorer prognosis and survival rates compared to patients with higher levels (p < 0.0001). Moreover, the diagnostic and prognostic potential of miR-320a correlated with clinicopathological characteristics such as tumor size, tumor node metastasis (TNM) stage, and lymph node metastasis. Functionally, depletion of miR-320a in human A549 lung adenocarcinoma cells induced their metastatic potential and reduced apoptosis, which was reversed by exogenous re-expression of miR-320a mimics, indicating that miR-320a has a tumor-suppressive role in NSCLC. These results were further supported by high levels of epithelial-mesenchymal transition (EMT) marker proteins (e.g., Beta-catenin, MMP9, and E-cadherin) in lung cancer cells and tissues via immunoblot and immunohistochemistry experiments. Moreover, through bioinformatics and dual-luciferase reporter assays, we demonstrated that AKT3 was a direct target of miR-320a. In addition, AKT3-associated PI3K/AKT/mTOR protein-signaling pathways were elevated with down-regulated miR-320a levels in NSCLC. These composite data indicate that circulating miR-320a may function as a tumor-suppressor miRNA with potential as a prognostic marker for NSCLC patients.